Recovering an electromagnetic obstacle by a few phaseless backscattering measurements. (15th February 2017) - Li, Jingzhi; Liu, Hongyu; Wang, Yuliang
Abstract: We consider the electromagnetic scattering from a convex polyhedral PEC or PMC obstacle due to a time-harmonic incident plane wave. It is shown that the modulus of the far-field pattern in the backscattering aperture possesses a certain local maximum behavior. Using the local maximum indicating phenomena, one can determine the exterior unit normal directions, as well as the face areas, of the front faces of the obstacle. Then we propose a recovery scheme of reconstructing the obstacle by phaseless backscattering measurements. This work significantly extends our recent study in Li and Liu (2014 preprint) from two dimensions and acoustic scattering to the more challenging three dimensions and electromagnetic scattering.